Hubungan Antara Kejadian Bronkopneumonia Pada Anak Dengan Status Perubahan Psikoemosi Dan Perilaku Orang Tua Dalam Merawat Anak Bronkopneumonia - Adriana Panggoa; Alfunnafi Fahrul Rizal (Borneo Nursing Journal (BNJ), 2026)
Abstrak Bronkopneumonia merupakan salah satu penyebab utama morbiditas dan mortalitas pada anak, terutama balita. Organisasi Kesehatan Dunia (WHO) melaporkan pneumonia menyumbang sekitar 15% seluruh kematian balita di dunia. Indonesia kasus pneumonia pada balita tahun 2022 sebesar 38,8%, Provinsi Papua tahun 2022 juga mencatat 2.147 kasus pneumonia pada balita, terdiri atas 1.172 kasus pada balita laki-laki dan 975 kasus pada balita perempuan. data rekam medis Rumah Sakit Tk. II 17.05.01 Marthen Indey, jumlah kasus bronkopneumonia pada anak tahun 2025 mencapai 165 kasus, pada periode Januari-Maret tahun 2026 ditemukan 47 kasus. Penelitian ini menggunakan desain kuantitatif analitik dengan pendekatan cross-sectional. Sampel sebanyak 53 orang tua yang memiliki anak dengan diagnosis bronkopneumonia diambil menggunakan teknik total sampling. Data dikumpulkan melalui rekam medis dan kuesioner DASS-21, kemudian dianalisis secara univariat dan bivariat menggunakan uji Chi-Square dengan tingkat signifikansi α = 0,05. Hasil menunjukkan sebagian besar responden berusia 20-35 tahun (54,7%), berpendidikan SD (37,7%), dan bekerja sebagai ibu rumah tangga maupun swasta (masing-masing 32,1%). Sebagian besar anak berusia 1-3 tahun (77,4%). 36 responden anaknya mengalami bronkopneumonia sebanyak 23 responden (63,9%), memiliki kondisi psikoemosional adaptif dan 13 responden (36,1%) memiliki kondisi maladaptif. Hasil uji Chi-Square menunjukkan nilai p-value = 0,49 (p > 0,05), sehingga tidak terdapat hubungan yang signifikan antara kejadian bronkopneumonia pada anak dengan status perubahan psikoemosi orang tua. Tidak terdapat hubungan yang bermakna antara kejadian bronkopneumonia pada anak dengan status perubahan psikoemosi orang tua dalam merawat anak bronkopneumonia. Kata kunci: bronkopneumonia, anak, psikoemosional, orang tua, perilaku perawatan, DASS-21. Abstract Bronchopneumonia is one of the leading causes of morbidity and mortality in children, particularly under five years of age. The World Health Organization (WHO) reports that pneumonia accounts for approximately 15% of all deaths among children under five worldwide. In Indonesia, the prevalence of pneumonia cases among under-fives in 2022 was 38.8%. In the same year, Papua Province recorded 2,147 pneumonia cases in under-fives, consisting of 1,172 cases in boys and 975 cases in girls. Medical record data from Tk. II 17.05.01 Marthen Indey Hospital shows that the number of bronchopneumonia cases in children reached 165 cases in 2025, while 47 cases were recorded during the January–March period of 2026. This study employed an analytical quantitative design with a cross-sectional approach. A sample of 53 parents of children diagnosed with bronchopneumonia was selected using a total sampling technique. Data were collected through medical records and the DASS-21 questionnaire, followed by univariate and bivariate analysis using the Chi-Square test with a significance level of . The results revealed that the majority of respondents were aged 20–35 years (54.7%), had an elementary school education (37.7%), and worked as housewives or private sector employees (32.1% each). Most of the children were aged 1–3 years (77.4%). Among the 36 respondents whose children experienced bronchopneumonia, 23 respondents (63.9%) demonstrated adaptive psychoemotional conditions, while 13 respondents (36.1%) exhibited maladaptive conditions. The Chi-Square test results yielded a p-value of 0.49 (), indicating no significant relationship between the incidence of bronchopneumonia in children and the status of parents' psychoemotional changes. There is no significant relationship between the incidence of bronchopneumonia in children and the status of parents' psychoemotional changes in caring for children with bronchopneumonia. Keywords: bronchopneumonia, children, psychoemotional, parents, caregiving behavior, DASS-21. Abstract Bronchopneumonia is one of the leading causes of morbidity and mortality in children, particularly under five years of age. The World Health Organization (WHO) reports that pneumonia accounts for approximately 15% of all deaths among children under five worldwide. In Indonesia, the prevalence of pneumonia cases among under-fives in 2022 was 38.8%. In the same year, Papua Province recorded 2,147 pneumonia cases in under-fives, consisting of 1,172 cases in boys and 975 cases in girls. Medical record data from Tk. II 17.05.01 Marthen Indey Hospital shows that the number of bronchopneumonia cases in children reached 165 cases in 2025, while 47 cases were recorded during the January–March period of 2026. This study employed an analytical quantitative design with a cross-sectional approach. A sample of 53 parents of children diagnosed with bronchopneumonia was selected using a total sampling technique. Data were collected through medical records and the DASS-21 questionnaire, followed by univariate and bivariate analysis using the Chi-Square test with a significance level of . The results revealed that the majority of respondents were aged 20–35 years (54.7%), had an elementary school education (37.7%), and worked as housewives or private sector employees (32.1% each). Most of the children were aged 1–3 years (77.4%). Among the 36 respondents whose children experienced bronchopneumonia, 23 respondents (63.9%) demonstrated adaptive psychoemotional conditions, while 13 respondents (36.1%) exhibited maladaptive conditions. The Chi-Square test results yielded a p-value of 0.49 (), indicating no significant relationship between the incidence of bronchopneumonia in children and the status of parents' psychoemotional changes. There is no significant relationship between the incidence of bronchopneumonia in children and the status of parents' psychoemotional changes in caring for children with bronchopneumonia. Keywords: bronchopneumonia, children, psychoemotional, parents, caregiving behavior, DASS-21.